SYSTEM FOR CONTROL,EVALUATIONAND VISUALIZATIONOF THE PHYSICAL DEVELOPMENT OF YOUNG MALETAEKWONDO ATHLETES - D. Avramov (Trakia Journal of Sciences)
PURPOSE: The purpose of this study is to create a normative tables for control and evaluation of the physical development in taekwondo according to the age groups of the World Taekwondo Federation. METHODS: Seven standard physical tests were used to measure the physical development of 208 male taekwondo athletes. The tests we used were: 1. Stand and reach, 2. Split, 3. Modified T-test, 4. Vertical jump, 5. Push-ups –30 seconds, 6. Sit-ups –30 seconds, 7. Squat jumps –30 seconds. The method of Sigma digressions was used for creating the ranking scales. RESULTS: On the basis of our results specific tables were designed for each test and age group with the use of a 7, 20 and 50-grade (point) scale. The input and visualization were automated into a graphic file for easier comprehension. CONCLUSIONS: The resultsof our study are a starting point for creating a database for taekwondo. They can also serve as a basis for overall evaluation system of taekwondo athletes. Such a system will provide a crucial feedback about the efficiency of the training methods, the current physical condition of the athletes and will be of motivational use for taekwondo practitioners.